Elimination of Poverty Through Islamic System of Sadaqaat: Research Study - Ahmad, Dr. Hafiz Muhammad; Haider, Dr. Ghulam (Al-Amīr Research Journal for Islamic Studies, 2023)
Islam is a complete code of life. Economic teachings of Holy Qur’an and Hazrat Muhammadﷺ are comprehensive. Allah Almighty guides us how to spend money in His way. There are two types of Sadaqaat. Sadaqaat-e-Wajibah are compulsory on wealthy people with certain ratio while Sadaqaat-e-Nafilah are optional. Holy Prophetﷺ encouraged his followers to help the needy. Eradication of poverty is the main goal of Islamic system of Sadaqaat. In this research paper an analytical study is made to know how economic issues of the poor are addressed by Islamic economic system. There is dire need to understand different kinds of Sadaqaat. If the government and the public feel their responsibilities and follow Islam, poverty can be eliminated from society. This article addresses the problems of poverty. Moreover, it is also told how the poor should be looked after. Key words: Holy Qur’an, Holy Prophet ﷺ, Economy, Sadaqaat, Poverty.